Influence of Inocule Dose and Fermentation Time of Lactobacillus acidophilus on Characteristics and Antioxidants of Soyghurt Black Soybean (Glycine soja (L) Merrit) - Ningrumsari, Ida; Iskandar, Ende; Herlinawati, Lina; Hodijat, Asep (RA Journal Of Applied Research, 2022)
Black soybeans have been underutilized because of their black color. The purpose of this research is to make black soybean soyghurt containing antioxidants with a research design using a factorial completely randomized design (CRD). Existing data were collected and then processed by analysis of variance (Anava). If there is a significant difference with the control, then it is continued with Duncan's multiple distance test. The results showed that there was an effect between the inoculum dose and fermentation time on an increase in protein by 175%, a decrease in water content by 11.15% and an increase in antioxidants by 55% and a decrease in pH by 41%. The level of preference for black soybean soyghurt is on average to like it very much on taste, while in terms of texture, color, aroma and thickness, it is like to like it a bit.